1261. Antimicrobial Activity of Aztreonam-Avibactam against Gram-negative Bacteria Isolated from Patients Hospitalized with Pneumonia in Europe, Latin America, and Asia in 2019. (31st December 2020) - Sader, Helio S; Castanheira, Mariana; Carvalhaes, Cecilia G; Doyle, Timothy B; Mendes, Rodrigo E
Abstract: Background: Aztreonam (ATM) is a monobactam stable to hydrolysis by metallo-β-lactamases (MBL). Avibactam (AVI) is a non-β-lactam β-lactamase inhibitor that inhibits serine carbapenemases (CPEs), such as ESBLs, KPCs, AmpC, and some OXAs. ATM-AVI is under clinical development for treatment of serious infections caused by Gram-negative bacteria (GNB), including MBL-producers. Methods: 2, 582 GNB (1, 630 Enterobacterales [ENT] and 952 nonfermentative-GNB) were consecutively collected (1/patient) from 56 medical centers located in Western Europe (W-EU; 22 centers in 10 nations), Eastern Europe (E-EU; 12 centers in 9 nations), Latin America (LATAM; 10 centers 6 nations), and the Asia-Pacific region (APAC; 12 centers in 8 nations) in 2019 and susceptibility (S) tested against ATM-AVI and comparators at a central laboratory by reference broth microdilution methods. Results: Overall, 99.9% of ENT (MIC50/90, 0.06/0.25 mg/L), including 99.1% of carbapenem-resistant ENT (CRE; MIC50/90, 0.25/0.5 mg/L), were inhibited at an ATM-AVI MIC of ≤ 8 mg/L (Table). CRE rates were 1.4%, 23.7%, 6.3%, and 9.6% in W-EU, E-EU, LATAM, and APAC, respectively (6.9% overall). A CPE was identified in 95 of 113 CRE isolates (84.1%). These CPEs included NDM-like (31.0% of CRE), KPC-like (26.5%), OXA-48-like (24.8%), and VIM-like (7.1%). Six isolates produced 2 CPEs. The highest ATM-AVI MIC value among MBL-producers (n=43; MIC50/90, 0.12/0.5 mg/L) was 4 mg/L. Among P. aeruginosa, 75.1% were inhibited at ≤ 8 mg/L of ATM-AVI; S to meropenem (MEM), piperacillin-tazobactam, and ceftazidime were 69.4%, 72.5%, and 75.7%, respectively, and ranged from 64.3% in E-EU to 82.0% in W-EU. MEM non-S P. aeruginosa varied from 22.2% in W-EU to 54.8% in E-EU. ATM-AVI was highly active against S. maltophilia, inhibiting 95.0%, 100.0%, 100.0%, and 90.0% of isolates from W-EU, E-EU, LATAM, and APAC, respectively, at ≤8 mg/L. S. maltophilia S to cotrimoxazole were 90.0%, 97.7%, 85.7%, and 100.0% in W-EU, E-EU, LATAM, and APAC, respectively. ATM-AVI also was very active against Burkholderia spp. (highest MIC, 8 mg/L). Conclusion: Our results support clinical development of ATM-AVI to treat pneumonia caused by ENT (including MBL-producers), P. aeruginosa, S. maltophilia, and Burkholderia spp. Table 1 Disclosures: Helio S. Sader, MD, PhD, A. Menarini Industrie Farmaceutiche Riunite S.R.L. (Research Grant or Support)Allergan (Research Grant or Support)Allergan (Research Grant or Support)Allergan (Research Grant or Support)Cipla Ltd. (Research Grant or Support)Cipla Ltd. (Research Grant or Support)Melinta (Research Grant or Support)Merck (Research Grant or Support)Merck (Research Grant or Support)Paratek Pharma, LLC (Research Grant or Support)Pfizer (Research Grant or Support) Mariana Castanheira, PhD, 1928 Diagnostics (Research Grant or Support)A. Menarini Industrie Farmaceutiche Riunite S.R.L. (Research Grant or Support)Allergan (Research Grant or Support)Allergan (Research Grant or Support)Amplyx Pharmaceuticals (Research Grant or Support)Cidara Therapeutics (Research Grant or Support)Cidara Therapeutics (Research Grant or Support)Cipla Ltd. (Research Grant or Support)Cipla Ltd. (Research Grant or Support)Fox Chase Chemical Diversity Center (Research Grant or Support)GlaxoSmithKline (Research Grant or Support)Melinta Therapeutics, Inc. (Research Grant or Support)Melinta Therapeutics, Inc. (Research Grant or Support)Melinta Therapeutics, Inc. (Research Grant or Support)Merck (Research Grant or Support)Merck (Research Grant or Support)Merck & Co, Inc. (Research Grant or Support)Merck & Co, Inc. (Research Grant or Support)Paratek Pharma, LLC (Research Grant or Support)Pfizer (Research Grant or Support)Qpex Biopharma (Research Grant or Support) Cecilia G. Carvalhaes, MD, PhD, A. Menarini Industrie Farmaceutiche Riunite S.R.L. (Research Grant or Support)Allergan (Research Grant or Support)Cidara Therapeutics (Research Grant or Support)Cipla Ltd. (Research Grant or Support)Fox Chase Chemical Diversity Center (Research Grant or Support)Melinta Therapeutics, Inc. (Research Grant or Support)Merck (Research Grant or Support)Merck (Research Grant or Support)Merck & Co, Inc. (Research Grant or Support)Pfizer (Research Grant or Support) Timothy B. Doyle, Allergan (Research Grant or Support)Allergan (Research Grant or Support)Cipla Ltd. (Research Grant or Support)Melinta Therapeutics, Inc. (Research Grant or Support)Pfizer (Research Grant or Support)Qpex Biopharma (Research Grant or Support) Rodrigo E. Mendes, PhD, A. Menarini Industrie Farmaceutiche Riunite S.R.L. (Research Grant or Support)Allergan (Research Grant or Support)Allergan (Research Grant or Support)Basilea Pharmaceutica International, Ltd (Research Grant or Support)Cipla Ltd. (Research Grant or Support)Department of Health and Human Services (Research Grant or Support)GlaxoSmithKline (Research Grant or Support)Melinta Therapeutics, Inc. (Research Grant or Support)Merck (Research Grant or Support)Merck (Research Grant or Support)Pfizer (Research Grant or Support)